PERENCANAAN ULANG DESAIN PARKIR PASAR BULU KOTA SEMARANG - Kamil Safari Kusuma Atmaja; Dimas Ariya Asmara Putra; YI. Wicaksono; Amelia Kusuma Indriastuti (Jurnal Karya Teknik Sipil, 2013)
Nowadays the progress of Semarang city is getting rapid, many shop centers rises in Tugu Muda area. Most of people use their car or motorbike to do their activities through those streets. This condition caused the higher mobility each year and makes parking lots become important thing in transportation system. The necessary of parking lot should be available, The bigger traffic volume makes bigger necessary of parking lot. If it does not enough, cars may take the spaces beside of road to park, and this caused some disruptions to others. Redesigning the park design focused on one the biggest traditional market in Semarang one of them is Bulu market at Mgr Soegijapranoto street. The method used in this redesign is plat matching method for data retrieval parking , Linier regretion method and the queuing theory to data processing and the parking design. Primary data that is required in this analysis is parking duration, and service system. And for the secondary data required the amount of vehicles out – vehicles in at the market, the amount of traders at the market, the amount of resident at each subdistricts of Semarang city, and area of the market. The conclusion, the parking lot design, 117 SRP to car and 502 SRP to motorcycle, can provide the customers need in parking at the market. The design can be predicted that it will be resisted in five years based on growing ratio between city parking lot and Bulu market parking lot.